Slowed decay of mRNAs enhances platelet specific translation - Mills, Eric W. (Blood, 2017)
Platelets are anucleate cytoplasmic fragments that lack genomic DNA, but continue to synthesize protein using a pool of messenger RNAs (mRNAs), ribosomes, and regulatory small RNAs inherited from the precursor megakaryocyte (MK). The regulatory processes that shape the platelet transcriptome and the full scope of platelet translation have remained elusive. Using RNA sequencing (RNA-Seq) and ribosome profiling of primary human platelets, we show the platelet transcriptome encompasses a subset of transcripts detected by RNA-Seq analysis of in vitro–derived MK cells and that these platelet-enriched transcripts are broadly occupied by ribosomes. We use RNA-Seq of synchronized populations of in vitro–derived platelet-like particles to show that mRNA decay strongly shapes the nascent platelet transcriptome. Our data suggest that the decay of platelet mRNAs is slowed by the natural loss of the mRNA surveillance and ribosome rescue factor Pelota.